The role of hormones of the adrenal cortex in regulation of the muscular activity of a growing organism - M.V. Shaykhelislamova; N.B. Dikopolskaya; G.A. Bilalova; N.H. Mansour; T.L. Zefirov (Учёные записки Казанского университета: Серия Естественные науки)
We studied the endocrine mechanisms of urgent and long-term adaptation of children to increased physical stresses and, in particular, the role of hormones of the adrenal cortex in the regulation of the muscular activity of male athletes aged 11–15 years old. The relevance of the study is determined by the immaturity and functional instability of the hypothalamic-pituitary-adrenal system in children, its physiological hyperfunction during the adolescent period, which, when exposed to high muscular loadings, increases the risk of evolutionary processes transition to the endocrine dysfunction of adolescence. However, in most studies, the secretory activity of adrenal cortex is considered only as an indicator of fitness.